THE ROLE OF ARCHITECTURE IN EASTERN ARTS (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
This article is devoted to the formation and development of the tradition of literary studies. In this, the life of kulyots during its history, its origin and stages of development, historical development, types of kulyots, specific characteristics; integral and differential aspects of such genres as kachkul, majmua, bayoz, tazkira were analyzed.